Verbal advantage 10 easy steps to a powerful vocabulary - Elster, Charles Harrington (new york random house, 2000)
this book provides far more than a set of words to try to memorize. this comprehensive, graduated program helps you remember key words, use them in your daily life, and increase your rate of learning new words
American corner
includes bibliographical references and index
11
Keywords: English language; Vocabulary